Factor associated with experience of modern contraceptive use before pregnancy among women who gave birth in Kersa HDSS, Ethiopia. (December 2016) - Musa, Abdulbasit; Assefa, Nega; Weldegebreal, Fitsum; Mitiku, Habtamu; Teklemariam, Zelalem
Abstract Background Worldwide, every year 289, 000 women die related to pregnancy and its complications. Nearly, all of these deaths occur in developing countries and more than half of this deaths occur in sub-Saharan Africa. Report suggested that using contraceptives can reduce this maternal mortality by 44 %. Even if, Ethiopia is one of the countries with highest maternal mortality, only 41 % of married women are using family planning. This analysis aimed at assessing factor associated with experience of contraceptive use before pregnancy among women who gave birth in Kersa Health and Demographic Surveillance System, Ethiopia. Methods This study was part of data generated for Kersa Health and Demographic Surveillance System. Women who gave birth during October 2011 to September 2012 were asked whether they had used contraceptive before getting their last pregnancy. Data were collected by using Kersa Health and Demographic Surveillance System questionnaire. Both bi-variate and multivariate analysis were used to identify associated factors. Results The proportion of modern contraceptive before pregnancy among the study participants was found to be 383 (40.9 %). The most commonly used modern contraceptives was Injectable contraceptive 270 (70.0 %) followed by oral contraceptives, 66 (17.23 %). Modern contraceptive use was negatively association with being Muslim (AOR = 0.2, 95 % CI = 0.05, 0.72) and being young mother (AOR = 0.44, 95 % CI = 0.22, 0.86). Rural town residence (AOR = 2.23, 95 % CI = 1.15, 4.35) was found to have positive association with utilization of modern contraceptives. Conclusions Among women giving birth, only a minority had attempted to delay or prevent their recent birth by using contraception. Being young, being Muslim and living in rural area were significantly associated with low utilization of modern contraceptive. Increasing family planning education and involving religious leaders in family planning promotion would improve utilization of modern contraceptive use.